H3F3A K27M mutations in thalamic gliomas from young adult patients - Aihara, Koki (Oxford University Press, 2014)
INTRODUCTION: Mutations in H3F3A, which encodes histone H3.3, commonly occur in pediatric glioblastoma. Additionally, H3F3A K27M substitutions occur in gliomas that arise at midline locations (eg, pons, thalamus, spine); moreover, this substitution occurs mainly in tumors in children and adolescents. Here, we sought to determine the association between H3F3A mutations and adult thalamic glioma. METHODS: Genomic H3F3A was sequenced from 20 separate thalamic gliomas. Additionally, for 14 of the 20 gliomas, 639 genes—including cancer-related genes and chromatin-modifier genes—were sequenced, and the Infinium HumanMethylation450K BeadChip was used to examine DNA methylation across the genome. RESULTS: Of the 20 tumors, 18 were high-grade thalamic gliomas, and of these 18, 11 were from patients under 50 years of age (median age, 38 y; range, 17–46), and 7 were from patients over 50 years of age. The H3F3A K27M mutation was present in 10 of the 11 (91%) younger patients and absent from all 7 older patients. Additionally, H3F3A K27M was not detected in the 2 diffuse astrocytomas. Further sequencing revealed recurrent mutations in TP53, ATRX, NF1, and EGFR. Gliomas with H3F3A K27M from pediatric or young adult patients had similar, characteristic DNA methylation profiles. In contrast, thalamic gliomas with wild-type H3F3A had DNA methylation profiles similar to those of hemispheric glioblastomas. CONCLUSION: We found that high-grade thalamic gliomas from young adults, like those from children and adolescents, frequently had H3F3A K27M.